"I Don't Know and I Don't Want to Know": A Qualitative Examination of Older African American Women's Knowledge and Experiences With HIV. (October 2018) - Belgrave, Faye Z.; Javier, Sarah J.; Butler, Deborah; Dunn, Chelsie; Richardson, Joann; Bryant, Lindsay
While older African American women (e.g., aged 50 years and older) comprise only 11% of the female population in the United States, they account for 50% of HIV diagnoses among women in this age group. Unique sociocultural factors, including a lack of HIV knowledge and stigma, contribute to HIV risk among older African American women. The goal of this qualitative study was to obtain a nuanced perspective from older African American women about HIV knowledge and experiences with HIV using the framework of intersectionality theory. Focus groups were conducted with 35 African American women who were 50 years and older, nonpartnered, and heterosexual. Women were asked what they knew about HIV and if they thought older women were at risk for HIV. A thematic analysis using NVivo 11 yielded two central themes and three subthemes: HIV knowledge, including experiential knowledge, superficial knowledge, and no knowledge, and stigma around HIV in the Black church. Implications for developing HIV prevention programs and testing messages are discussed.